Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 41675 by Raj Singh last updated on 11/Aug/18

Commented by math khazana by abdo last updated on 12/Aug/18

I = ∫    (dx/(1+((cosx)/(sinx)))) = ∫   ((sinx)/(sinx +cosx)) dx  =_(tan((x/2))=t)    ∫    (((2t)/(1+t^2 ))/(((2t)/(1+t^2 ))+((1−t^2 )/(1+t^2 )))) ((2dt)/(1+t^2 )) =∫   ((2t)/(2t+1−t^2 )) ((2dt)/(1+t^2 ))  = ∫  ((4t)/((1+t^2 )(−t^2  +2t +1)))dt =−∫  ((4t dt)/((t^2  +1)(t^2 −2t−1)))  let decompose F(t) =((4t)/((t^2  +1)(t^2  −2t−1)))  roots of  t^2 −2t−1  Δ^′  = 1−(−1) =2 ⇒t_1 =1+(√2)  and t_2 =1−(√2)  F(t)=((4t)/((t^2  +1)(t−t_1 )(t−t_2 )))  = (a/(t−t_1 )) +(b/(t−t_2 )) +((ct +d)/(t^2  +1))  a = ((4t_1 )/((t_1 ^2  +1)(2(√2)))) =((2t_1 )/((√2)(t_1 ^2 +1))) =((2+2(√2))/((√2)(4+2(√2))))  =((1+(√2))/((√2)(2+(√2))))  b = ((4t_2 )/((t_2 ^2  +1)(−2(√2)))) =((4(1−(√2)))/((4−2(√2))(−2(√2))))  =((1−(√2))/((2−(√2))(−(√2)))) =(((√2)−1)/((√2)(2−(√2))))  ...be continued...

I=dx1+cosxsinx=sinxsinx+cosxdx=tan(x2)=t2t1+t22t1+t2+1t21+t22dt1+t2=2t2t+1t22dt1+t2=4t(1+t2)(t2+2t+1)dt=4tdt(t2+1)(t22t1)letdecomposeF(t)=4t(t2+1)(t22t1)rootsoft22t1Δ=1(1)=2t1=1+2andt2=12F(t)=4t(t2+1)(tt1)(tt2)=att1+btt2+ct+dt2+1a=4t1(t12+1)(22)=2t12(t12+1)=2+222(4+22)=1+22(2+2)b=4t2(t22+1)(22)=4(12)(422)(22)=12(22)(2)=212(22)...becontinued...

Answered by tanmay.chaudhury50@gmail.com last updated on 11/Aug/18

∫(dx/(1+cotx))  ∫((sinx)/(sinx+cosx))dx  =(1/2)∫((cosx+sinx−(cosx−sinx))/(sinx+cosx))dx  =(1/2)[∫dx−∫((cosx−sinx)/(sinx+cosx))dx  =(1/2)[∫dx−∫((d(sinx+cosx))/(sinx+cosx))]  =(1/2)[x−ln(sinx+cosx)]+c

dx1+cotxsinxsinx+cosxdx=12cosx+sinx(cosxsinx)sinx+cosxdx=12[dxcosxsinxsinx+cosxdx=12[dxd(sinx+cosx)sinx+cosx]=12[xln(sinx+cosx)]+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com